Combatting antibiotic-resistant bacteria using nanomaterials. (21st November 2018) - Gupta, Akash; Mumtaz, Shazia; Li, Cheng-Hsuan; Hussain, Irshad; Rotello, Vincent M.
Abstract : Nanomaterials as self-therapeutic agents and drug-delivery vehicles for antimicrobial therapies. Abstract : The dramatic increase in antimicrobial resistance for pathogenic bacteria constitutes a key threat to human health. The Centers for Disease Control and Prevention has recently stated that the world is on the verge of entering the "post-antibiotic era", one where more people will die from bacterial infections than from cancer. Recently, nanoparticles (NPs) have emerged as new tools that can be used to combat deadly bacterial infections. Nanoparticle-based strategies can overcome the barriers faced by traditional antimicrobials, including antibiotic resistance. In this tutorial review, we have highlighted multiple nanoparticle-based approaches to eliminate bacterial infections, providing crucial insight into the design of elements that play critical roles in creating antimicrobial nanotherapeutics. In particular, we have focused on the pivotal role played by NP-surface functionality in designing nanomaterials as self-therapeutic agents and delivery vehicles for antimicrobial cargo.